40 UMP staff and students visited Al Hijrah TV station to learn more about broadcasting - UMP, PNC (2019)
In a move to further strengthen the branding campaign of Universiti Malaysia Pahang (UMP), the Vice-Chancellor Office (PNC) organised a trip to the Al Hijrah television station on January 15, 2019.